PERANAN ASPEK KEBERSIHAN PRODUKSI DAN KEHALALAN DI USAHA MIKRO RAHAYU KOTA SUBARAYA - Zakariya Zakariya; Kunto Inggit Gunawan; Mataji Mataji (JPM17: Jurnal Pengabdian Masyarakat, 2019)
The micro business owner Rahayu with the mek "Pelita Hati" is located on Jl.PandugoVI / 7 Surabaya. This business was established since 2001 and is engaged in bakingbusiness. The produced types of cakes: nastar, syringe cake, peanut cake, cheese cake, chocolatecake, bowl cake, various types of bread and various kinds of pudding.The issue of Rahayu micro business includes:a. Production capacity has not fully met demand.b. Need to increase production capacity.Not able to make a business bookkeeping.c. Limited capital.d. Not yet have the ability to market online and have not fulfilled the administrativesystem.e. Need efficient business planning.The purpose of this activity is:a. To increase motivation, to be able to make clean and halal production.b. To improve the performance of Rahayu Surabaya micro business.The method of carrying out counseling and counseling material includes:a. The principle of cleanliness of production.b. Understanding the principles of sharia-based production cleanliness "i.c. Understand Japanese management principles in the cleanliness of production.d. Work hard.e. Religious spirit in language.Before the test was done, it was expected to occur:a. Increased understanding of hygiene aspects in carrying out production activities whichinclude: understanding aspects of work hygiene, compliance cleanliness, andcleanliness of the work environment.b. Improved Halal aspects which include: Halal use of raw materials for production, halalobtaining tools and their use, and not damaging the environment in production.Keyword: micro business - cleanliness production â€“ halalÂ  production